The association between non-alcoholic fatty liver disease and atopic dermatitis: a population-based cohort study - Gau, Shuo-Yan; Huang, Ching-Hua; Yang, Yih; Tsai, Tung-Han; Huang, Kuang-Hua; Lee, Chien-Ying (Frontiers in Immunology, 2023)
Background In previous studies, it was reported that non-alcoholic fatty liver disease (NAFLD) incidence and prevalence increased in children with atopic dermatitis. Nevertheless, the actual association between the two diseases has not been fully proven in large-scale studies, and real-world evidence is missing. The objective of this nationwide, longitudinal cohort study was to evaluate the association between NAFLD and atopic dermatitis. Methods The National Health Insurance Research Database in Taiwan was utilized in this study. Patients with records of NAFLD diagnosis were recruited as the experimental group, and patients having less than three outpatient visits or one inpatient visiting record due to NAFLD were excluded from the study design. Non-NAFLD controls were matched based on a 1:4 propensity score matching. Potential confounders including age, gender, comorbidity, and medical utilization status were considered as covariates. The risk of future atopic dermatitis would be evaluated based on multivariate Cox proportional hazard regression. Results Compared with people without NAFLD, a decreased risk of atopic dermatitis in NALFD patients had been observed (aHR = 0.93, 95% CI 0.87–0.98). The trend was especially presented in young NAFLD patients. In patients younger than 40 years old, a 20% decreased risk of atopic dermatitis was reported (aHR = 0.80, 95% CI 0.70–0.92). Conclusion People with NAFLD were not associated with an increased risk of atopic dermatitis. Conversely, a 0.93-fold risk was noted in NAFLD patients, compared with NAFLD-free controls. Future studies are warranted to evaluate further the mechanism regarding the interplay between the inflammatory mechanisms of NAFLD and atopic dermatitis.